2021
DOI: 10.3390/brainsci11070920
|View full text |Cite
|
Sign up to set email alerts
|

Upper Limb Motor Planning in Individuals with Cerebral Palsy Aged between 3 and 21 Years Old: A Systematic Review

Abstract: Individuals with cerebral palsy have difficulties performing activities of daily living. Beyond motor execution impairments, they exhibit motor planning deficits contributing to their difficulties. The objective of this review is to synthesize the behavioral evidence of motor planning deficits during an upper limb motor task in children, adolescents and young adults with cerebral palsy aged between 3 and 21 years. Methods: The inclusion criteria were: (1) including individuals with cerebral palsy from 3 to 21 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 148 publications
2
4
0
Order By: Relevance
“…Thus, additional torque was applied after lift-off to further minimize roll. The anticipatory control of forces and torque is in line with prior studies that demonstrated children with USCP generally have intact anticipatory control of kinetics in the less-affected hand [7,16,17,27].…”
Section: Children With Uscp Have Anticipatory Control Of Digit Forces and Torquesupporting
confidence: 86%
See 2 more Smart Citations
“…Thus, additional torque was applied after lift-off to further minimize roll. The anticipatory control of forces and torque is in line with prior studies that demonstrated children with USCP generally have intact anticipatory control of kinetics in the less-affected hand [7,16,17,27].…”
Section: Children With Uscp Have Anticipatory Control Of Digit Forces and Torquesupporting
confidence: 86%
“…The biomechanical disadvantage of not using the passive lever arm in order to account for subsequent actions is in line with past studies that demonstrated impairments relating to kinematic scaling and end-state comfort in the less-affected hand [1,2,7,16,17]. This is comparable to previous studies where a multi-step action was performed such as placing a cylinder on a shelf [6], where children with USCP are able to grasp the object, but do not account for what will be done with the object (i.e., place a cylinder on a shelf, or in this study to keep the object level).…”
Section: Children With Uscp Demonstrated a Maladaptive Digit Placement Strategysupporting
confidence: 83%
See 1 more Smart Citation
“…Indeed, it is well-described that children with uCP can have motor planning de cits. 19 Hence, investigating motor planning in relation to this task, as well as which is the preferred condition is needed to further understand how children with uCP plan and coordinate both hands.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent review on upper limb motor planning in CP, only 3.5% of individuals in included studies had bilateral CP. 9 Similarly, in another review on the evaluation and characterization of manual function, 23% of participants had bilateral CP. 10 However, the disproportionate focus on upper limb function in unilateral CP does not signify that manual function is not impaired in bilateral CP.…”
Section: Introductionmentioning
confidence: 96%